Performance characteristics of growing rabbits fed glicidia sepium leaf meal as a replacement for groundnut (1999)
The study involved 16 weaner crossbred (New Zealand White and Chinchila) rabbits of about eight weeks of a.fetz with initial average weight of 0.69 kg. The animals were offered a measured amount of their respective diets. The level of replacement of groundnut cake with Gliricidia leaf meal (GLM) were 0, 25 50 and 75%, to give four diets which were fed ad libitum throughout the experimental period of 35 days. The similar average daily feed intake of the rabbit fed 0, 25 and 50% GLM included diets was significantly (P < 0.05) higher than the corresponding daily weight gain of the rabbits fed 25 and 50% GLM diets and those fed 75% GLM diet recorded the least (P < 0.05) daily gain. Dry matter intake (DMI) was significantly correlated with daily weight gain (r = 0.94, P < 0.05) and feed efficiency (r = 0.90, P < 0.05).